Diagenetic Facies Division of Different Types of Sandstone Reservoirs and Their Differentiation - Zhang, Dalong (Scientific Journal of Technology, 2025)
In response to the increasing proportion of low-porosity, low-permeability, and tight sandstone reservoirs in current oil and gas exploration, this paper conducts a systematic study on diagenetic facies division. First, the development stages and existing problems of diagenetic facies research are reviewed, with an emphasis on the objective of establishing a scientific classification system. The study highlights the core criteria for facies division, including types and intensities of diagenesis, petrographic characteristics, pore and petrophysical features, as well as logging responses and quantitative models. Differentiated emphasis is proposed for reservoirs of different types. Finally, a general methodological framework is constructed, progressing “from micro to macro, from qualitative to quantitative,” providing systematic ideas and methodological support for diagenetic facies research and favorable zone prediction in various types of reservoirs.